Association Between Tegmen Tympani Status and Superior Semicircular Canal Pattern. Issue 1 (January 2016) - Whyte, Jaime; Tejedor, Maria Teresa; Fraile, Jesús José; Cisneros, Ana; Crovetto, Rafael; Monteagudo, Luis Vicente; Whyte, Ana; Crovetto, Miguel Angel
Abstract : Objective: Detecting and quantifying the possible association between tegmen tympani (TT) status and superior semicircular canal (SSC) pattern. Design: Observational study. Setting: Study conducted in three tertiary Spanish hospitals. Patients: Nonselected consecutive patients of all ages (607 temporal bones). Interventions: Thin-section multidetector row computed axial tomography (CAT scan) of the temporal bones. Main Outcome Measure: Thickness of SSC bone coverture adjacent to the middle fossa, and TT status as a dichotomous variable: dehiscence (TTD) or integrity (TTI). Results: The observed SSC patterns were dehiscence (3.79%), papyraceous or thin (11.20%), normal (76.77%), thick (4.94%), and pneumatized (3.29%). The observed TT statuses were TTD (10.87%) and TTI (89.13%). TTD was associated with SSCD and papyraceous patterns, and TTI percentages were higher in normal and thick patterns ( χ 2 = 11.102; p = 0.001). The TTD probability was estimated as a function of SSC pattern and age by a multivariate binary logistics regression model ( χ 2 = 45.939; p < 0.001). Conclusion: SSC pattern was significantly associated with TT status. Age influenced this association. The risk for TTD increased by 4.1% per each year of increasing age, did not differ significantly for normal and thick patterns, and increased 12 times and 20 times for papyraceous and SSCD patterns, respectively.